The major satellite DNA families of the diploid Chenopodium album aggregate species: Arguments for and against the "library hypothesis" - Belyayev, Alexander; Jandová, Michaela; Josefiová, Jiřina; Kalendar, Ruslan; Mahelka, Václav; Mandák, Bohumil; Krak, Karol (PloS one, 2020)
Satellite DNA (satDNA) is one of the major fractions of the eukaryotic nuclear genome. Highly variable satDNA is involved in various genome functions, and a clear link between satellites and phenotypes exists in a wide range of organisms. However, little is known about the origin and temporal dynamics of satDNA. The "library hypothesis" indicates that the rapid evolutionary changes experienced by satDNAs are mostly quantitative. Although this hypothesis has received some confirmation, a number of its aspects are still controversial. A recently developed next-generation sequencing (NGS) method allows the determination of the satDNA landscape and could shed light on unresolved issues. Here, we explore low-coverage NGS data to infer satDNA evolution in the phylogenetic context of the diploid species of the Chenopodium album aggregate. The application of the Illumina read assembly algorithm in combination with Oxford Nanopore sequencing and fluorescent in situ hybridization allowed the estimation of eight satDNA families within the studied group, six of which were newly described. The obtained set of satDNA families of different origins can be divided into several categories, namely group-specific, lineage-specific and species-specific. In the process of evolution, satDNA families can be transmitted vertically and can be eliminated over time. Moreover, transposable element-derived satDNA families may appear repeatedly in the satellitome, creating an illusion of family conservation. Thus, the obtained data refute the "library hypothesis", rather than confirming it, and in our opinion, it is more appropriate to speak about "the library of the mechanisms of origin".
Keywords: vysoce účinné nukleotidové sekvenování; Genome, Plant; diploidie; druhová specificita; Diploidy; satelitní DNA; Gene Library; Species Specificity; Evolution, Molecular; DNA, Satellite; Chenopodium album; genom rostlinný; DNA, Plant; fylogeneze; DNA rostlinná; Phylogeny; High-Throughput Nucleotide Sequencing; genová knihovna; molekulární evoluce